Subregional growth poles of the Opole Voivodeship. The case study of the Kędzierzyn-Strzelce subregion - Kantor, Dariusz (Subregionalne bieguny wzrostu województwa opolskiego. Studium przypadku subregionu kędzierzyńsko-strzeleckiego, 2016)
The main objective of this paper is to present the organization of subregional growth poles of the Opole Voivodeship, especially the Kędzierzyn-Strzelce subregion in the context of increasing the efficiency of local government units constituting the subregions in implementing the National Spatial Development Concept 2030 and the Opole Voivodeship development policy by 2020
Biblioteka Regionalisty, 2016, Nr 16, s. 29-36
Keywords: growth pole; cohesion policy; local self-government; association; biegun wzrostu; polityka spójności; samorząd terytorialny; stowarzyszenie